Mobilization & traction principles and techniques - Prentice, William E ([St. Louis, Mo.] : Mosby, 1993)
(Producer) This presentation is an introduction to the principles and techniques of mobilization and traction, a manual therapy approach for the rehabilitation of many sport-related injuries. This approach to mobilization and traction involves the biomechanics of joint movement and incorporates the relationship between physiological and accessory motion. The goal of mobilization and traction techniques is to improve joint mobility and reduce pain by restoring accessory movements to the joint or reducing joint hypermobility
William, Prentice
Keywords: Physical Therapy Techniques -- methods; Athletic Injuries -- rehabilitation; Manipulation, Orthopedic -- methods